Comparative analyses of persistence traits in Escherichia coli O157:H7 strains belonging to different clades including REPEXH01 and REPEXH02 strains - Carter, Michelle Qiu; Carychao, Diana; Bono, James L. (Frontiers in Microbiology, 2024)
Recent application of whole genome sequencing in the investigation of foodborne illness outbreaks has facilitated the identification of Reoccurring, Emerging, or Persistent (REP) bacterial strains that have caused illnesses over extended periods of time. Here, the complete genomes of two Escherichia coli O157:H7 (EcO157) outbreak strains belonging to REPEXH01 and REPEXH02, respectively, were sequenced and annotated. Comparative genomics and phenotypic analyses were carried out to identify REP-associated traits. The REPEXH01 strain PNUSAE013245 belonged to clade 8 and shared >96% CDSs with the 2006 spinach-associated outbreak strain EC4115. A 79-Kb genomic island was identified only in PNUSAE013245, and encoded functions related to heavy metals and antibiotic resistances. The REPEXH02 strain PNUSAE043864 belonged to clade 2, like the 2006 Taco John’s restaurants-associated outbreak strain TW14588 and the REPEXH02 strain 2019C-3201. These three strains differed mainly in plasmids and prophages repertoire. Unlike 2019C-3201, PNUSAE043864 carried only the virulence plasmid pO157; unlike TW14588, PNUSAE043864 carried one Stx2a-encoding prophage. Phenotypic assays revealed that all clade 2 strains produced greater amounts of biofilms than the clade 8 strains, although there were no significant differences in adhesion of EcO157 to romaine lettuce. The persistence of EcO157 was further evaluated by quantifying populations of culturable cells, persisters, and Viable But Not Culturable (VBNC) cells for strains inoculated in river water and incubated at 15°C for 14 weeks. The fractions of culturable cells were comparable among the strains tested until 10 weeks post inoculation, when the three clade 2 strains exhibited significantly greater survival than strain PNUSAE013245. The population of persisters for all strains except PNUSAE013245 increased when the incubation time increased and reached up to 24–30% of the total culturable cells. The population of VBNC increased for all strains during the incubation and reached up to 65–80% of the total population. Both persisters and VBNC cells represent the dormancy state of pathogen cells that have increased tolerance to antibiotics and sanitizers. Presence of high portions of persisters and VBNC cells in agricultural environments highlights the need to understand the physiology of bacterial pathogens in leafy greens production environments and the challenges in developing effective control strategies.